Influence of sport and season period on the dietary intake of adolescent rowers and kayakers - Reguant, A.; Terrados, N. (Archivos de medicina del deporte, 2008)
Dietary habits of adolescent athletes could change depending on sports and nutritional advice. The purpose of the present study was to investigate dietary habits of elite adolescents from two different sports, one of them with weight limitations (rowing and kayaking) living at the same training camp and eating the same sport menus, at the beginning of a training season and at the beginning of the competition season. Methods: 10 elite junior rowers and 15 elite junior kayakers (age: 16±1,3), were studied using a 72 hours nutritional recording (3-day food record method), and anthropometric measurements at the two periods of the season; initial training period (INIT) and competition period (COMP). Results: Mean daily carbohydrate intake was lower than recommended, protein and fat intake was above recommended in both rowers and kayakers (43 and 45; 22 and 21; 34 and 33%, respectively). Total fat intake was above 30% in all participants, and saturated-fat intake was above 25% in all of them. Energy intake was the same at INIT and COMP in kayakers (2342±638 kcal and 2153±616 kcal), but decreased in rowers (2585±592 kcal and 1969±591 kcal) with a decrease in lipids intake and an increase in carbohydrate intake. Conclusions: Young athletes from different sports, even following the same menus and eating at the same place, could have different dietary habits, some of them erroneous. Young rowers during the competition period decrease their energy intake, mainly through a reduction in fat intake. In young athletes training camps, not only is necessary to have supervised sports menus but also a daily eating room control. These adolescent should be encouraged to maintain their energy intake during the competition periods.